A blinded observational cohort study of the microbiological ecology associated with pyuria and overactive bladder symptoms - Gill, Kiren (Int Urogynecol J, 2018)
INTRODUCTION AND HYPOTHESIS: This study sought to characterise the microbial ecology of the lower urinary tract in patients with symptoms of overactive bladder (OAB) using culture of the urinary urothelial cell sediment. The pathological significance of the microbiome was assessed through its relationship with known urothelial inflammatory markers and patient reported symptoms. METHODS: Adult female patients with OAB symptoms and asymptomatic controls were assessed at 12 study visits scheduled every 4 weeks. At each visit, all participants provided a clean-catch midstream urine (MSU) that was analysed to count white and uroepithelial cells, submitted to standard culture and spun urothelial-cell-sediment culture. Symptoms were assessed using validated questionnaires. RESULTS: This analysis shows that OAB patients differ consistently from controls, demonstrating differences in bacterial ecology (t −4.57, p 0.0001), in the microscopic pyuria count (t −6.37, p 0.0001) and presence of infected urothelial cells (t −4.21, p 0.0001). The primary outcome measure of bacterial growth [colony-forming units (CFU) ml(−1)] was higher in OAB patients than in controls throughout the 12 months. Data showed a correlation between symptoms and pyuria, with notable urgency correlating with pyuria and epithelial cell shedding. The routine urine cultures (with a threshold of reporting a positive result as 10(5) CFU/ml) were unable to distinguish OAB patients from controls. However, sediment cultures differed significantly, and there was a correlated increased immune response amongst OAB patients. CONCLUSIONS: This study supports the need to re-examine the OAB phenotype given this association with microbial colonisation.